Draft Genome of the Asian Buffalo Leech Hirudinaria manillensis - Guan, De-Long; Yang, Jie; Liu, Ying-Kui; Li, Yuan; Mi, Da; Ma, Li-Bin; Wang, Zhe-Zhi; Xu, Sheng-Quan; Qiu, Qiang (Frontiers in Genetics, 2020)
The Asian Buffalo leech, Hirudinaria manillensis, is an aquatic sanguivorous species distributed widely in Southeast Asia. H. manillensis has long been used clinically for bloodletting and other medical purposes. Recent studies have focused on artificial culturing, strain optimization, and the identification and development new drugs based on the anticoagulant effects of H. manillensis bites; however, data regarding its genome remain unclear. This study aimed to determine the genome sequence of an adult Asian Buffalo leech. We generated a draft assembly of 151.8 Mb and a N50 scaffold of 2.28 Mb. Predictions indicated that the assembled genome contained 21,005 protein-coding genes. Up to 17,865 genes were annotated in multiple databases including Gene Ontology. Sixteen anticoagulant proteins with a Hirudin or Antistasin domain were identified. This study is the first to report the whole-genome sequence of the Asian Buffalo leech, an important sanguivorous leech of clinical significance. The quality of the assembly is comparable to those of other annelids. These data will help further the current understanding of the biological mechanisms and genetic characteristics of leeches and serve as a valuable resource for future studies.